'Knitting needles, knotting shuttles, & Totums & Cards & Counters': The Bluestockings and the Material Culture of Fibre Arts. (3rd July 2019) - Pohl, Nicole
Abstract : In this paper I want to tease out threads in the socio-economic narrative of fibre arts by using the case study of the Bluestocking Circle, in particular Elizabeth Montagu (1718–1800), Mary Delany (1700–1788) and Montagu's sister, Sarah Scott (1721–1795). To contrast these lives through the lens of material culture, we can identify needlework and textiles as a subtle marker of social mobility and disparities in wealth within one social circle (the Bluestockings) and family. Whilst Mary Delany combined scientific interest with technical skills, Elizabeth Montagu commissioned decorative fibre arts, such as her famous feather work, for public display, and her sister Sarah Scott, forced by diminished social and economic circumstances, concentrated on practical dress-making and alteration and appliqué. Both sisters, though born into the same family, thus developed very different textile skill sets. The production of textiles carried class markers in terms of what kind of work was produced and what kind of materials and techniques were used. Thus, fibre arts, like fashion, were 'an emblem of material self-advancement, [and] … a badge of moral worth' (John Styles, The Dress of the People (New Haven: Yale University Press, 2007), p. 60) .